Evolving Scripts: A Comprehensive Review of Chinese Writing Reforms - Rinne, Ville (My University, 2024)
This thesis discusses the history of the Chinese writing system and the possibility of phonetizising the Chinese language. The thesis first describes the development of Romanization systems and other alternative phonetic writing systems for Chinese, starting from missionary influence and continuing to the development of Pinyin in the 1950s. The thesis then discusses different opinions regarding the possibility of replacing Chinese characters with Pinyin and the pros and cons of using Chinese characters. The conclusion of this thesis is that although Chinese characters have their advantages, like crossing the barriers between different Chinese dialects due to their independence from their pronunciation (Monroy, 2022), and although they are significant for the Chinese culture (Cao, 2024), learning to write thousands of characters and remembering them puts a burden for learning to read and write Chinese, even for natives (Moser, 2006), (Moser, 2016). However, although an alphabetic system would be more convenient, full replacement of the characters with Pinyin is unlikely to happen soon because it would be met with resistance and would require changes to the structure of the language (Moser, 2006).

Tämä opinnäytetyö käsittelee Kiinan kirjoitusjärjestelmän historiaa ja kiinan kielen fonetisoinnin mahdollisuutta. Opinnäytetyö kuvailee ensin romanisointijärjestelmien ja muiden vaihtoehtoisten foneettisten kirjoitusjärjestelmien kehitystä, alkaen lähetyssaarnaajien vaikutuksesta ja jatkuen Pinyinin kehitykseen 1950-luvulla. Tämän jälkeen opinnäytetyössä pohditaan erilaisia mielipiteitä kiinalaisten merkkien korvaamisesta Pinyinillä sekä kiinalaisten kirjainten käytön eduista ja haitoista. Tämän opinnäytetyön johtopäätös on, että vaikka kiinalaisilla merkeillä on etunsa, kuten eri Kiinan murteiden välisten esteiden ylittäminen, koska merkit ovat riippumattomia ääntämismuodostaan (Monroy, 2022), ja vaikka ne ovat tärkeitä kiinalaiselle kulttuurille (Cao, 2024), tuhansien merkkien kirjoittamisen opettelu ja niiden muistaminen rasittaa kiinan kielen lukemisen ja kirjoittamisen oppimista jopa alkuperäisasukkaille (Moser, 2006), (Moser, 2016). Silti, vaikka aakkosjärjestelmä olisikin kätevämpi, merkkien täydellinen korvaaminen Pinyinillä ei todennäköisesti tapahdu pian, koska se kohtaisi vastustusta ja vaatisi muutoksia kielen rakenteeseen (Moser, 2006).
Keywords: Chinese writing system, Chinese characters, Chinese alphabetization, Writing reform, Pinyin.